The apple of discord: can spider cocoons be equipped with antimicrobial factors?—a systematic review - Mateusz Glenszczyk; Artur Lis; Weronika Porc; Magdalena Pacwa-Płociniczak; Agnieszka Babczyńska (Frontiers in Zoology)
Abstract The antimicrobial properties of spider silk have been a topic of scientific intrigue since ancient times. Despite extensive research, the question remains unresolved due to conflicting findings and methodological challenges. This work revisits and synthesizes current knowledge, proposing that spider cocoons, rather than other spider products, serve as a particularly promising focus for investigating antimicrobial factors. This emphasis arises from their critical role in parental investment and reproductive success, as the maternal care associated with spider egg sacs suggests the necessity for enhanced antimicrobial protection to safeguard offspring. By investigating existing research, we propose that the protective properties of spider egg sacs may derive not only from the silk itself, but also from the eggs contained within, as supported by previous hypotheses. Furthermore, drawing on the body of knowledge, we suggest that potential antimicrobial defense mechanisms may extend beyond intrinsic factors, encompassing interactions with microorganisms, plants, and other possible environmental elements that remain unexplored but may likely be interconnected. This review highlights that the potential interplay of these factors may be complex and possibly influenced by ecological and biological contexts. Unraveling these dynamics requires an interdisciplinary approach, incorporating diverse methodologies and perspectives to address the gaps in current knowledge. By refining the focus and embracing a broader conceptual framework, future research can provide definitive insights into the antimicrobial properties of spider cocoons. Resolving this long-standing question will not only clarify the scientific debate but also deepen our understanding of spider biology and the adaptive strategies that have evolved to ensure reproductive success.